Involvement of interlukin-17A (IL-17A) gene polymorphism and interlukin-23 (IL-23) level in the development of peri-implantitis - Ehab Qasim Talib; Ghada Ibrahim Taha (Nature Publishing Group, 2024)
Abstract Background Dental implantation has been practiced since ancient times and has gone through several stages. Dentists use dental implants to support dental prostheses such as crowns, bridges, dentures, face prostheses, or as an orthodontic anchor. Thus, the purpose of this study is to detect the role of the immune-genetic variation of IL-17A and related inflammatory cytokine (IL-23) in the initiation and progress of peri implantitis. Material and methods This cross-sectional study included 80 subjects (15 peri-implantitis patients, 35 successful implants, and 30 healthy controls); their mean age was (43.91 ± 11.33) years. Blood samples and Peri-implant sulcus fluid (PISF) were collected from all subjects (patients with peri-implantitis, successful implants, and healthy controls) attending the Department of Oral and Maxillofacial Surgery in the Dental College Teaching Hospital, Baghdad University, Baghdad, Iraq. The blood sample detects gene polymorphisms in interleukin-17A by a polymerase chain reaction (PCR). An enzyme-linked immunosorbent assay (ELISA) was carried out to estimate the Peri-implant sulcus fluid (PISF) levels of interleukin-23. Result The current study revealed an obvious significant elevation in the mean level of interleukin-23 in the peri-implantitis patient's group more than its level in the successful implant and control groups (P < 0.05). In addition, the result showed that A/A genotype is associated significantly with peri-implantitis OR (95%confidence interval) =6.9 (1.7121 to 27.4638) folds increase risk of peri-implantitis) (p = 0.0065), while G/A genotype had OR 4.9 (0.9539-24.9394) folds increased risk of peri-implantitis, (p = 0.0572). But it was not statistically significant and G/G genotype had a one-fold increase risk of peri-implantitis. Conclusion The increased level of inflammatory cytokine (interleukin-23) might add to the systemic inflammatory burden a predisposing factor, which may lead to impaired osseointegration and subsequent bone loss or implant failure. In addition, IL-17A gene polymorphism may play a role in peri-implant disease susceptibility, especially in persons carrying the rs2275913 A allele at a higher risk of developing peri-implantitits as compared with those carrying the G allele.